Work-Family Balance or Greedy Organizations? - Burchielli, Rosaria; Bartram, Timothy; Thanacoody, Rani (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2008)
This paper re-examines the concept of work-family balance by analyzing qualitative data from interviews conducted with Australian senior female staff and managers at a major metropolitan bank and a large, regional hospital. Extant research suggests that managers and staff in senior roles, who have greater autonomy and discretion than other employees, are better able to balance their work and family demands. This paper finds evidence for work-family conflict among participants, who perceive they have “no balance” and must make many personal sacrifices to meet the conflicting demands of work and family. Our findings are confronted with the greedy institutions framework which provides a suitable metaphor to understand the role of organizations in supporting the dual demands of work-family.